Effect of arm swing direction on forward and backward jump performance - Hara, M.; Shibayama, A.; Arakawa, H.; Fukashiro, S. (Journal of Biomechanics, 2008)
This study quantified and compared how the directional differences in arm swing affected mechanical and physiological parameters during forward and backward jumping. Seven subjects maximally performed three types of forward and backward squat jumps—no arm swing (FJ, BJ), forward arm swing (FJF, BJF), and backward arm swing (FJB, BJB) from a force platform. All performances were captured with a 3-D motion capture system. Electromyograms (EMGs) of the lower extremity muscles were obtained. Variables were calculated by combining kinematic and kinetic data. The jump displacement and center of mass velocity at take-off were significantly larger in FJF than in FJ or FJB and larger in BJB than in BJ or BJF, suggesting that the best performance was obtained by employing the same arm swing direction as a given jump direction. The total work by three lower and two upper extremity joints was significantly larger in FJF than in FJ or FJB and larger in BJB than in BJ or BJF. For the lower extremity joints, hip work was the greatest in FJF and BJB. The integrated EMG of the biceps femoris when the hip power was produced was significantly larger in FJF and BJB than under other conditions. These results suggest that if the arm swing direction is the same as a given jump direction, the activation level of the hip extensor is greater to counter large loads which make the hip joint flex during the push-off phase, which result in increased hip extension torque, power, and work.